2018
DOI: 10.1080/02670836.2017.1376428
|View full text |Cite
|
Sign up to set email alerts
|

Structure and orientation relationship of new precipitates in a Cu–Cr–Zr alloy

Abstract: The crystallography and morphology of the nano-sized precipitate particles in a ternary Cu–Cr–Zr alloy were studied by transmission electron microscopy. A new type of face-centred-cubic (f.c.c) Cr-rich precipitate was observed. This precipitate is ordered and solute enriched on alternate {110} f.c.c planes, with an ellipsoid-shaped morphology. The new orientation relationship (OR) between the precipitate and Cu matrix satisfies [211]M//[011]p and [100]M//[111]p, {-111}M//{200}p and {02-2}M//{02-2}p. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…3. Highly similar observations were reported in the literature [5,12,32,39,40]. In these reports, such particles were identified as Cr clusters.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…3. Highly similar observations were reported in the literature [5,12,32,39,40]. In these reports, such particles were identified as Cr clusters.…”
Section: Resultssupporting
confidence: 89%
“…The size of the Cr cluster (diameter 3.3-2.5 nm), as determined by SANS and HAADF-STEM, falls within the range of those assessed by many authors [12,18,39,40]. The volume fraction found by SANS is in agreement with the initial Cr content of the alloys, indicating the precipitation of all Cr atoms.…”
Section: Resultssupporting
confidence: 84%
“…As previously mentioned, the SADP analysis (Figure 7) indicated that the disc-shaped precipitates formed during aging in the Cu–Cr–Ag alloy were fcc Cr-rich phases (lattice parameter is about 0.423 nm), which is consistent with previous observations for Cu–Cr alloy [14] and Cu–Cr–Zr alloys [15,26]. Furthermore, the precipitates in Cu–Cr alloys were identified as Cr-rich clusters by Chbihi et al using APT [13].…”
Section: Discussionsupporting
confidence: 90%
“…4), but they become incoherent with over-ageing and thus tend towards 3. This has been independently observed by TEM on peak-aged and overaged samples (Batra et al, 2003;Chen, Jiang, Liu et al, 2018;Jha et al, 2021). Note that coherent and incoherent here refer to the condition of the precipitate interface, not the type of neutron-nucleus interaction.…”
Section: Resultsmentioning
confidence: 59%